John gave his son mike 5z number of coins in addition to what he already has. mike then has (y + 10) times as many coins as he had originally. in terms of y and z, how many coins did mike have originally? explanation
Let X be the number of coin Mike has originally. Hi father gave him 5z got so he will have now: [tex]X+5z[/tex]. The sentence "mike then has (y + 10) times as many coins as he had originally" can be written in math form like this: [tex]X+5z=(y+10)X[/tex] We will solve the above equation for X like this: [tex]X+5z=(y+10)X\\X-(y+10)X=-5z\\X(1-(y+10))=-5z\\X(-y-9)=-5z\\X=\dfrac{-5z}{-y-9}
[/tex] Mike has originally [tex]\dfrac{5z}{y+9}[/tex] coins.